2019
DOI: 10.1111/jth.14350
|View full text |Cite
|
Sign up to set email alerts
|

Novel short peripheral catheter design for prevention of thrombophlebitis

Abstract: Phlebitis is one of the most frequent complications related to short peripheral catheters (SPC). A new SPC design, aimed for minimizing mechanical phlebitis, was tested in vivo in swine. MRI analysis revealed 40% less inflammation with the new SPC design compared to commercial SPC. The results confirm that our SPC biomechanical design approach can minimize phlebitis rates. Summary BackgroundShort peripheral catheters (SPCs) are the most common intravenous device in today's medical practice. Short peripheral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 36 publications
(46 reference statements)
2
15
0
Order By: Relevance
“…14 Another study in an animal model found that modi cation of the catheter with the goal of reducing contact against the vein wall led to a 40% reduction in subcutaneous edema. 18 In our study, not only did we identify that subcutaneous edema existed in the majority of our insertions, but we also found that subcutaneous edema on ultrasound was a signi cant predictor of PIVC failure, a key clinical outcome measure. However, unlike previous investigations, we tracked onset and progression of subcutaneous changes using an innovative methodology inclusive of daily ultrasound site assessments.…”
Section: Discussionsupporting
confidence: 52%
“…14 Another study in an animal model found that modi cation of the catheter with the goal of reducing contact against the vein wall led to a 40% reduction in subcutaneous edema. 18 In our study, not only did we identify that subcutaneous edema existed in the majority of our insertions, but we also found that subcutaneous edema on ultrasound was a signi cant predictor of PIVC failure, a key clinical outcome measure. However, unlike previous investigations, we tracked onset and progression of subcutaneous changes using an innovative methodology inclusive of daily ultrasound site assessments.…”
Section: Discussionsupporting
confidence: 52%
“…We followed the histopathological methods reported in a previous study investigating a novel PIVC design. Weiss et al (19) also inserted 20 G BD Insyte PIVCs into the veins of porcine ears, however their study lasted 12 days, compared to our 2-day study, with typical clinical practice indicating PIVC usage for short-term administration of fluids and medication (2-3 days) in critical conditions requiring mechanical ventilation and critical care management.…”
Section: Discussionmentioning
confidence: 77%
“…All physical prototyping was performed at a specialised catheter manufacturing facility (Medical Murray, IL, USA). Similar to a previous study (19), we decided to modify a commercial device to allow a true comparison of the FloRamp with an existing PIVC. We chose the 20 G BD Insyte™ winged 45 mm long catheter (Becton Dickenson, Franklin Lakes, NJ, USA), as the BD Insyte is widely used and familiar to most infusion therapists.…”
Section: Methodsmentioning
confidence: 99%
“…Recent exploratory literature has suggested that subcutaneous edema represents more than a compromised or leaking vein due to infiltration. Instead, subcutaneous edema may represent a local inflammatory reaction due to ongoing mechanical and chemical insults to the vein wall [ 10 , 13 , 14 ]. Strategies targeting a reduction of subcutaneous edema may improve PIVC survival.…”
Section: Discussionmentioning
confidence: 99%
“…In an analysis on the location of catheter tip position within the vein, Murayama et al found that contact of the tip against the vein wall was associated with subcutaneous edema on ultrasound [ 10 ]. Another study in an animal model found that modifying the catheter within the vein to reduce contact against the vein wall led to a 40% reduction in subcutaneous edema [ 14 ]. Our data and these findings suggest that modification of the PIVC tip position is likely another key component in reducing early catheter failure.…”
Section: Discussionmentioning
confidence: 99%